Planning and managing the physician workforce - Schoenbaum Stephen C (Israel Journal of Health Policy Research, 2012)
Abstract National planning and management of the physician workforce is a multifaceted, difficult, and even controversial activity. It is an important subset of overall health workforce planning and management, which contributes to a country's having an effective and efficient health care system. This commentary builds on a new survey of specialty considerations by Israeli medical students early in their clinical training, places it in the broader context of health workforce planning, and provides examples of some approaches and activities being taken in the United States that are applicable to other developed countries. This is a commentary on http://www.ijhpr.org/content/1/1/13.